Structural Dynamics of Thrombin-Binding DNA Aptamer d(GGTTGGTGTGGTTGG) Quadruplex DNA Studied by Large-Scale Explicit Solvent Simulations - Reshetnikov, Roman; Golovin, Andrey; Spiridonova, Vera; Kopylov, Alexei; Šponer, Jiří (Journal of chemical theory and computation, 2010)
The thrombin-binding aptamer (15-TBA) is a 15-mer DNA oligonucleotide with sequence d(GGTTGGTGTGGTTGG). 15-TBA folds into a quadruplex DNA (G-DNA) structure with two planar G-quartets connected by three single-stranded loops. The arrangement of the 15-TBA-thrombin complex is unclear, particularly with respect to the precise 15-TBA residues that interact with the thrombin structure. Our present understanding suggests either the 15-TBA single stranded loops containing sequential thymidines (TT) or alternatively a single-stranded loop, containing a guanine flanked by 2 thymidines (TGT), physically associates with thrombin protein. In the present study, the explicit solvent molecular dynamics (MD) simulation method was utilized to further analyze the 15-TBA-thrombin three-dimensional structure. Functional annotation of the loop residues was made with long simulations in the parmbsc0 force field. In total, the elapsed time of simulations carried out in this study exceeds 12 microseconds, substantially surpassing previous G-DNA simulation reports. Our simulations suggest that the TGT-loop function is to stabilize the structure of the aptamer, while the TT-loops participate in direct binding to thrombin. The findings of the present report advance our understanding of the molecular structure of the 15-TBA-thrombin structure further enabling the construction of biosensors for aptamer bases and the development of anticoagulant agents.